2017
DOI: 10.1155/2017/3230596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sanitary Conditions of Head Meat, Esophagus, Diaphragm Meat, and Boning Scrap Processing

Abstract: Enterobacteriaceae, coliforms, and Escherichia coli counts are important hygiene indicators and may be pathogenic. Thus, the aim of the present study was to determine microbiological contamination in head meat, the esophagus, diaphragm, and boning scraps and evaluate the hygienic conditions of the processing of these products. The Petrifilm5 (3M) method for determining Enterobacteriaceae, total coliforms, and E. coli was applied for 104 samples. APHA, European Union, PAHO/WHO, and Brazil/MAPA recommendations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
3
0
5
Order By: Relevance
“…In this context, microbiological evaluations performed on utensils, environment, and carcasses of cattle, pigs, and sheep in the slaughterhouse of Australia (Bakhtiary et al, 2016), in Mato Grosso (Santos et al, 2017) and Rio de Janeiro (Cabral et al, 2014), Brazil have been reported. In these studies, the occurrence of microorganisms was observed which are indicators of fecal contamination, belonging to the Enterobacteriaceae family, species such as Escherichia coli, and Salmonella enterica in utensils, environment, and carcasses indicating hygiene problems in the slaughter process.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, microbiological evaluations performed on utensils, environment, and carcasses of cattle, pigs, and sheep in the slaughterhouse of Australia (Bakhtiary et al, 2016), in Mato Grosso (Santos et al, 2017) and Rio de Janeiro (Cabral et al, 2014), Brazil have been reported. In these studies, the occurrence of microorganisms was observed which are indicators of fecal contamination, belonging to the Enterobacteriaceae family, species such as Escherichia coli, and Salmonella enterica in utensils, environment, and carcasses indicating hygiene problems in the slaughter process.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding beef products, the main contamination step occurs during hide removal, and several studies suggest that initial operation failures are responsible for the contamination of the final product (Elder and others ; Barkocy‐Gallagher and others ; Brichta‐Harhay and others ; Santos and others ). In addition, contamination may be present in fresh products, such as sprouts and lettuce, due to contamination from the use of manure or contaminated water‐based fertilizers (Verhaegen and others ).…”
Section: Introductionmentioning
confidence: 99%
“…This is currently especially true because of the recent events of the so-called "weak meat operation" that raised doubts about Brazilian meat safety. Thus, studies are being conducted to characterize and evaluate the contamination of this type of product in Brazil (SANTOS, et al 2017).…”
mentioning
confidence: 99%